A study to assess the Knowledge on Prevention of Human Papillomavirus (HPV) Infection among Adolescent Girls of selected college - Mrs. Niketa Vaghela; Mr. Vijay Khata; Ms. Nayna Zala; Ms. Kiran Rathva; Mr. Divyesh Nandaniya (The Bioscan, 2025)
Background: Human Papillomavirus (HPV) is a primary contributor to cervical cancer, particularly in developing nations such as India. Young girls frequently have insufficient knowledge regarding HPV transmission, preventive measures, and the significance of vaccination. This lack of awareness may elevate their susceptibility to infection. Evaluating their understanding is crucial for pinpointing deficiencies and advancing effective health education initiatives aimed at HPV prevention within educational environments. Aim: This study aimed to assess the Knowledge of Adolescent girls on the prevention of Human Papillomavirus (HPV) Infection and to find out the association between knowledge on the prevention of Human Papillomavirus (HPV) Infection among adolescent girls with their selected sociodemographic variables. Methods: A quantitative research methodology featuring a descriptive design was employed to evaluate the understanding of Human Papillomavirus (HPV) infection prevention among adolescent females. The research took place in a chosen para-medical college. By utilizing a non-probability purposive sampling method, adolescent girls aged 12 to 19 years who provided consent were included in the study, whereas those who declined or male students were excluded. Data collection tools included a structured knowledge questionnaire and an observational checklist. Results: The vast majority of adolescent girls (92.7%) were between the ages of 18 and 19, with a significant number enrolled in B.Sc. programs (57.3%) and living in rural regions (55.3%). The primary source of information regarding HPV was school or college (58.7%). Although 58% had heard of HPV before, only 46.7% exhibited a strong understanding, while 48% had an average level of knowledge. There was a statistically significant correlation between age and course with knowledge level (p=0.002 and p=0.0001, respectively), whereas factors such as residence, source of information, and prior awareness did not reveal significant correlations. Conclusion: The study found that age (p = 0.002) and course of study (p = 0.0001) had a significant association with HPV knowledge, with older girls and those from the B.Sc. Nursing course students’ backgrounds show better awareness. Other factors like residence, source of information, and prior awareness showed no significant association. There is a need for a structured teaching program to improve knowledge among adolescent girls regarding the prevention of HPV Infection. KEYWORDS: Human Papillomavirus (HPV), Knowledge Assessment, Adolescent Girl, HPV Infection, HPV Prevention, College Student.